Exposure of Underground Cable Intrusion Detection System to Transient Disturbances Caused by Nearby Lightning Strikes - Markowska, Renata (Elektronika ir Elektrotechnika, 2020)
Electronic systems with extensive underground cable installations are endangered by damage or interference during lightning as a result of current and voltage surges induced in the installations. The paper presents the study on the lightning threat to the electronic intrusion detection system based on underground cable sensors during a nearby lightning strike to the pole of the lighting system installed in parallel with the sensory cables. In the extensive intrusion detection system working in a network composed of several controller-sensor-terminator units, a problem arises whether the neighbouring units should or should not be connected galvanically in order the system is less vulnerable to the effects of a lightning electromagnetic pulse. The problem is complex since the threat level may depend on many factors, i.e. the point of the strike, the lightning current, soil parameters, and configurations of the affected systems. The problem has been studied using numerical simulations based on the electromagnetic field theory and method of moments. The results show that the isolated configuration, i.e. without the galvanic continuity between the units, may be better as far as relatively low soil resistivity and low steepness of the lightning current waveform are considered.